2020
DOI: 10.1177/1758835920980546
|View full text |Cite
|
Sign up to set email alerts
|

The association between immune-related adverse events and the prognosis of solid cancer patients treated with immunotherapy: a systematic review and meta-analysis

Abstract: Background: Immune-related adverse events (irAEs) are common during immune checkpoint inhibitor (ICI) treatment and reported to be associated with good survival. This study evaluated the association between onset timing of irAEs and survival of cancer patients treated with ICIs. Methods: Databases including PubMed, Embase, and the Cochrane library were systematically searched to retrieve clinical studies assessing the relationship between irAEs and survival in cancer patients with ICIs. The overall response ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 61 publications
1
6
0
Order By: Relevance
“…The lack of statistical significance in OS and PFS among patients with melanoma with grade 3 and above irAEs may be due to the increased mortality associated with higher side effects or glucocorticoid therapy. Our conclusions are consistent with previously published meta-analyses of all patients with cancer, suggesting a positive association between the occurrence of irAEs and PFS and OS, and the occurrence of irAEs may be a prognostic factor for patients with cancer treated with ICIs ( 19 23 , 86 ). Several studies have also found that the occurrence of low-grade irAEs, but not severe irAEs, is associated with better ICI outcomes in patients with cancer ( 19 , 23 , 88 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The lack of statistical significance in OS and PFS among patients with melanoma with grade 3 and above irAEs may be due to the increased mortality associated with higher side effects or glucocorticoid therapy. Our conclusions are consistent with previously published meta-analyses of all patients with cancer, suggesting a positive association between the occurrence of irAEs and PFS and OS, and the occurrence of irAEs may be a prognostic factor for patients with cancer treated with ICIs ( 19 23 , 86 ). Several studies have also found that the occurrence of low-grade irAEs, but not severe irAEs, is associated with better ICI outcomes in patients with cancer ( 19 , 23 , 88 ).…”
Section: Discussionsupporting
confidence: 93%
“…A total of 57 articles assessed the association between the occurrence of irAEs and OS in patients with melanoma ( 13 18 , 32 39 , 41 58 , 60 71 , 73 75 , 77 86 ), and 34 assessed PFS ( 14 , 15 , 18 , 32 , 34 , 36 42 , 47 , 49 , 54 , 55 , 58 60 , 62 , 64 , 66 , 68 72 , 75 , 76 , 78 , 79 , 81 , 82 , 85 ). Among these, the study of Abu-Sbeih et al.…”
Section: Resultsmentioning
confidence: 99%
“…With respect to AEs, our meta-analysis showed that vonoprazan had a significantly lower rate of adverse events than did PPIs. In contrast, the meta-analysis conducted by Xu et al [37] demonstrated that the incidence of adverse events was similar between vonoprazan and PPIs (P = 0.66). There are several differences between our meta-analysis and that of Xu et al [37] Only RCTs were included in our meta-analysis, while RCTs and cohort and single-arm studies were included in the meta-analysis by Xu et al [37] In addition, only patients with gastric ESD-induced ulcers were included in our meta-analysis, while patients with H. pylori infection, gastroesophageal reflux disease, peptic ulcer disease and ESD-induced ulcers were included in the meta-analysis by Xu et al [37] Notably, only seven RCTs were included for the comparison of adverse events in our meta-analysis.…”
Section: Discussionmentioning
confidence: 82%
“…17 Furthermore, there is ample published evidence that development of endocrinopathy, including thyroid dysfunction and hypophysitis, on immune checkpointbased treatment is predictive of improved survival for patients. 18,19 Most recently, a pooled analysis of combination chemotherapy with atezolizumab revealed that lower grade (1-2) toxicity in general was associated with OS benefit. 20 Ultimately, given the limited sample size in our study, it remains challenging to draw conclusions regarding specific toxicity rates from cross-trial comparisons.…”
Section: Discussionmentioning
confidence: 99%